Blurring boundaries: Exploring tweets as a legitimate journalism artifact. (May 2020) - Liu, Zhaoxi (Josie); Berkowitz, Dan
This study explores journalists' use of Twitter and what it means for their craft. Based on 8 weeks newsroom observation and more than a dozen in-depth interviews with reporters and editors at a big metro newspaper, the study found that journalists had contradicting views on whether or not to accept tweets, a form of snippet artifact, as a legitimate journalism artifact, leading to the blurring artifact boundary. Related, journalists faced uncertainties and ambiguities regarding the implications of such snippet artifact for the journalism craft and its core mission of informing the public.